SERVICE EXCELLENCE DEVELOPMENT USING THE INTEGRATION OF SERVQUAL, KANO MODEL, AND QUALITY FUNCTION DEPLOYMENT (QFD) AT A FOOD COURT IN PALEMBANG - Adnan Asadullah Samal, Muhammad
The food & beverage industry is one of the most promising industry sectors in Indonesia that has been highly developed and has a significant contribution to Indonesia’s GDP yet still has the potential to grow. The potential of the food & beverage sector attracts many industry players, thus the competition also increased. Given the increasing competition, the food & beverage industry must offer good quality services to customers and develop its competitive edge. In this research, an evaluation is carried out about the quality of service received by customers in a food & beverage industry namely KOKAS, a food court in Palembang. The quality of KOKAS services is evaluated by using the SERVQUAL method through a questionnaire that consists of 15 service quality attributes that are relevant to KOKAS. The findings of SERVQUAL show that there are 10 service quality attributes with a negative SERVQUAL gap and 5 service quality attributes that have a positive SERVQUAL gap. Then Kano model is used to classify the service quality attributes which in turn those indices are applied to compute the weights of the Quality Function Deployment (QFD) for a better understanding of the voice of the customer (VoC). The findings of the Kano model show that 4 service quality attributes are categorized as attractive, 3 service quality attributes are categorized as must-be, 6 service quality attributes are categorized as one-dimensional, and 2 service quality attributes are categorized as indifferent. Furthermore, there are 9 service quality attributes that are prioritized to be improved and these 9 service quality attributes are translated into technical requirements to obtain the appropriate service quality improvement strategies by using the House of Quality (HoQ). Keywords: Customer satisfaction; Food & beverage industry; SERVQUAL; Kano model; Quality function deployment.